KEPUTUSAN BERBELANJA ONLINE DI MASA PANDEMI - Yuwita Ariessa Pravasanti; Nanda Listiana Dita Saputri (LPPM ITB AAS Indonesia Surakarta, 2021)
The purpose and target of this community service are that this activity can add knowledge and skills to the community or potential consumers in shopping online. With sufficient knowledge, consumers can shop wisely, choose potential sellers/online stores, obtain product specifications according to their needs and desires, and obtain goods at low price levels, and minimize the risk of shopping online. Partners in this community service are the people of Sangup Village, Tamansari District, Boyolali Regency who have a Smartphone. To achieve the goals and targets of this PKM program, partners will be given training through a zoom application with materials: socialization of factors that influence consumers to shop online, ways and tips to shop online, and terms for shopping online, as well as risks and ways to reduce shopping risks on line, Keywords: Shopping, Consumer, Online